Photocatalytic Degradation of Aniline Using Supported TiO2/Charcoal Composite - Zhou, Yun-Long; Hu, Zhi-Biao; Tuo, Hong-Gui; Yang, Zeng-Ping (Asian Journal of Chemistry, 2014)
TiO2/bamboo charcoal composites were prepared by sol-gel technique with tetrabutyl titanate as the titanium source and 60-mesh bamboo charcoal as the support. The photocatalytic degradation processes of aniline were studied. The results indicated that the TiO2/bamboo charcoal composites had quite a good photocatalytic ability. In the UV irradiation, the temperature and pH value had great influence on the effect of degradation. When the pH value was between 1 to 3 and the temperature was 50 ºC, the degradation effects reached more than 93 %. The degradation rate of aniline decreased when the concentration increased but increased with more TiO2 in it. The degradation achieved balance after 105 min. The photocatalytic degradation of aniline to TiO2 fitted in with the first reaction kinetic equation.